An Interior Design Study of the General Reading Room at the Malang City Public Library and Regional Archives Service Based on the Third Place Concept - Nur Azmy Putri Maharani; Viola Malta Ramadhani Ramadhani (Darul Yasin Al Sys, 2026)
The formal spatial atmosphere of public libraries can constrain their social functions in supporting education and community engagement, particularly when users require flexible and adaptive environments for academic work, social interaction, discussion, and relaxation. This study aimed to analyze the potential application of the Third Place concept in creating a comfortable, educational, and community-responsive public space at the Malang City Public Library and Regional Archives Service. A design thinking approach was employed to evaluate existing spatial conditions and formulate interior design recommendations based on users’ activities and needs. The findings indicate that physical and visual comfort, spatial functionality, and facilities supporting the library’s role as a Third Place have not been fully optimized. Accordingly, this study proposes a spatial suitability concept for the General Reading Room comprising lounge, quiet, and discussion zones, complemented by administrative and transitional areas. The proposed arrangement accommodates diverse activities, including casual reading, academic and professional work based on a work-from-anywhere approach, informal interaction, and group discussion. The study concludes that a Third Place-based interior design can strengthen the library’s function as an inclusive and adaptable public space by integrating functional zoning with a more engaging and socially supportive atmosphere. This study contributes practical design recommendations for developing public libraries that encourage natural interaction, repeated use, and the formation of a community of regular visitors.